Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0237527
|View full text |Cite
|
Sign up to set email alerts
|

Climate change influences on the potential distribution of Dianthus polylepis Bien. ex Boiss. (Caryophyllaceae), an endemic species in the Irano-Turanian region

Abstract: Endemic and restricted-range species are considered to be particularly vulnerable to the effects of environmental change, which makes assessing likely climate change effects on geographic distributions of such species important to the development of integrated conservation strategies. Here, we determined distributional patterns for an endemic species of Dianthus (Dianthus polylepis) in the Irano-Turanian region using a maximum-entropy algorithm. In total, 70 occurrence points and 19 climatic variables were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…Due to its geographic location and socio-economic status, Malawi is most exposed to climate change [7], [8]. Thus understanding species' response to climate change is crucial in Malawi for agricultural land use planning, notably for high-value perennial crops [44], [49], [56]. Our predictions suggested that extensive areas in Malawi under the current climatic conditions are suitable for macadamia production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its geographic location and socio-economic status, Malawi is most exposed to climate change [7], [8]. Thus understanding species' response to climate change is crucial in Malawi for agricultural land use planning, notably for high-value perennial crops [44], [49], [56]. Our predictions suggested that extensive areas in Malawi under the current climatic conditions are suitable for macadamia production.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 120 orchards were sampled throughout Malawi, but for this study, a total of 36 points were used for the modelling purpose (Fig 3). The remaining 84 occurrence points were used for cross-validation to evaluate the predictive model accuracy [46]- [49].…”
Section: Occurrence Datamentioning
confidence: 99%
“…Climate change is considered as one of the most important issues globally, with shifting conditions affecting geographic distributions of plant species [1][2][3][4][5][6][7] . Studies of various plant species indicate that climate change may reduce the climatically suitable areas for species or shift their geographic distributions [8][9][10][11][12][13] . Investigating climate change impacts and the response of wild plant species to these changes is important for effective species conservation and sustainable ecological development 3,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of this species have focused on analysis of their essential oils 28,30−36 and hypnotic effects 33 ; however, no information has been assembled about the species' geographic distribution or environmental dimensions that shape these distributions. Since N. glomerulosa is a semi-endemic medicinal species that is widely used 37,38 , underlying likely the effects of climate change on its populations could be useful for conservation planning 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is concern that these changes caused by climatic fluctuations and anthropogenic-induced activities will increase extinction risks in one of six species [6]. Because of this, it is crucial to know the impacts of climate on the spatial distribution of endangered, endemic and range-restricted plants, ascertain the threat and develop suitable integrated conservation plans [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%